KEBIJAKAN LUAR NEGERI AMERIKA SERIKAT TERHADAP PROGRAM NUKLIR IRAN PADA MASA PEMERINTAHAN GEORGE WALKER BUSH DAN BARACK HUSSEIN OBAMA - LARASATI, MEUTIA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This thesis is structured to compare the US foreign policy towards Iran nuclear program under the administrations of 2 recent President of United States, George W. Bush (2001-2009) and Barack Obama (2009-present). To explain the focus of this study, this research is using a suitable conceptual framework to explain the research questions. Due to the focus of this research that is a comparison between the policy of 2 administrations, this research is using a Foreign Policy analysis in comparative study as a conceptual framework. The concept is consist of several aspects as an indicators in comparative study of policy. By using the concept of the FPA, this research shows that there are a difference and similarity in US Foreign Policy towards Iran's nuclear program during the administration of Bush and Obama . The difference occur in the Decision, or decree which refers to the option chosen by the leader to direct the policy itself. In this case, Bush chose to rely on a hard power, while Obama is pursuing a diplomacy method. This research proved that the difference on the decision is influenced by the individual factors. In this case, individual factors refers to the leader’s personality. The similarity occur on behavior. Behavior is a state-level analyze that refers to the implementation of the decision taken by leader. Both Bush and Obama’s administration using an economic sanction to oppress Iran. Based on the conceptual framework using to analyze, This research prove that the reason why both Bush and Obama’s administration using the same methods is because there are an internal resources which directs Obama administration to continue a policy which previously had taken by Bush